Bullying and undermining behaviours in surgery: A qualitative study of surgical trainee experiences in the United Kingdom (UK) & Republic of Ireland (ROI). (December 2020) - Clements, Joshua Michael; King, Martin; Nicholas, Rebecca; Burdall, Oliver; Elsey, Elizabeth; Bucknall, Vittoria; Awopetu, Ayoola; Mohan, Helen; Humm, Gemma; Nally, Deirdre M.; ,
Abstract: Background: Bullying and undermining (B/U) behaviours are documented in the international surgical workplace. This study is the largest assessment of prevalence of B/U behaviours within UK & ROI surgical training to date. Materials and methods: UK & ROI surgical trainees were electronically surveyed in July 2017. The survey was open for one month and sent to all registered trainees at Core and Specialty level by the Joint Committee on Surgical Training (JCST) along with email and social media dissemination by the Association of Surgeons in Training (ASiT) and the British Orthopaedic Trainees Association (BOTA). A consensus session on the topic was conducted at the ASiT Conference in Edinburgh in March 2018. Standards for reporting of Qualitative Research were followed. Results: 1412 responses were received (26.6% response rate). All training regions, grades and specialties were represented. 60% of trainees (n = 837) reported witnessing or experiencing B/U behaviours in the surgical workplace. The most common reports related to sexism; 42% (n = 568) reported witnessing or experiencing sexist language/attitudes in the workplace. This was reported more by female respondents (66% compared to 27% male). 21% (n = 291) and 13% (n = 180) reported witnessing or personally experiencing racist and homophobic language or attitudes respectively. Consultants were identified as the most frequent perpetrators. The surgical wards or theatres were the most frequently reported areas that trainees either witnessed or experienced B/U behaviours. Of those trainees who had reported a personal experience of B/U behaviours (n = 344), 20% described their experiences of reporting as negative or very negative. 48.1% of respondents felt that surgery as a whole had a moderate, high or very high degree of a concern about B/U behaviours. Conclusion: B/U behaviours are prevalent in the surgical domain. Urgent action is required to eradicate this unacceptable behaviour. A cross-specialty, intercollegiate response is required to tackle this issue and improve the working culture in surgery for all. Highlights: This study demonstrates a higher prevalence of bullying and undermining (B/U) than previously reported. 60% of trainees reported witnessing or experiencing B/U behaviours in the surgical workplace. Bullying and undermining behaviour was propagated by all members of the multidisciplinary team. Education and awareness of the magnitude of the problem through national campaigns are valuable. A zero-tolerance policy from governing bodies are essential in eradicating B/U behaviour.